Origins and Outcomes An Essay on the History of Student Aid in California. The Eureka Project: A Review of Student Financial Aid in California. - Eureka Project, Sacramento, CA.; Eureka Project, Sacramento, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1987)
The history of student aid policies in California is reviewed by the Eureka Project to help guide policy formation and review developments that have accounted for past consensus about the state's role in providing student aid. Attention is directed to: the demographic facts that have made student aid important to California; the evolution of concepts of student aid from its origins as a very small enterprise; the political and policy history of the major initiatives and trends in California's grant programs; and efforts to coordinate the increasing number of programs, especially state and federal ones. Topics reviewed in this document include: California population trends, older students and continuing education, social mobility and ethnic minorities, the concept of financial need, items in the student's budget, student resources, free tuition policy, high tuition costs at private colleges, aid before World War II, the GI Bill, prosperity and its aftermath, the origins of need analysis and its use in California, student aid packaging, the origins of the Basic Grant idea, the California State Scholarship Program, the College Opportunity Grant Program, achievement of ethnic diversity, the National Defense Education Act, and the Higher Education Act of 1965 and the 1972 Amendments. (SW)
Sponsoring Agency: Atlantic Richfield Foundation, Los Angeles, CA.
Sponsoring Agency: Weingart Foundation, Los Angeles, CA.
ERIC Note: Also sponsored by grants by James G. Irvine and Haynes Foundations.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational History; Federal Aid; Federal Legislation; Federal Programs; Federal State Relationship; Financial Policy; Grants; Higher Education; Need Analysis (Student Financial Aid); Political Influences; Population Trends; Scholarships; School Demography; State Aid; Student Financial Aid; California; Reports, Descriptive